A Hungarian Map-Maker in the Mexican-American Boundary Survey - Kökény, Andrea (Études sur la Région Méditerranéenne, 2023)
The Treaty of Guadalupe Hidalgo ended the U.S-Mexican War of 1846–1848 on February 2, 1848. The two countries agreed to send representatives to survey and mark a new international boundary from the Pacific Ocean to the Gulf of Mexico and create maps of it. The fieldwork lasted from the summer of 1849 to the fall of 1853. Just as the surveyors completed their work, however, a new treaty made parts of their survey irrelevant. The region of present-day southern Arizona and southwestern New Mexico was purchased by the United States for 10 million dollars in a treaty signed by James Gadsden, the American ambassador to Mexico at the time, on the 30th of December, 1853. The Gadsden Treaty had again called for the United States and Mexico to appoint surveyors, who carried out the fieldwork from November, 1854 to September, 1855. In the first half of my paper I propose to discuss the activity of the Boundary Commissions and their project of surveying and mapping the nearly two-thousand-mile border. The administrative center for the American Boundary Commission was in Washington D. C. It was directed by the topographical engineers who superintended the production of the boundary maps and the work of civilian clerks, who worked on computations, compilations, and drew all the finished maps. One of the map-makers was Károly László, a Hungarian engineer and surveyor, who drew five maps for the American and several others for the Mexican boundary commission. The second part of the paper will focus on his contribution and the characteristics of his identity.